$s = v_it + \frac{1}{2}at^2$

$h = v_it - \frac{1}{2}gt^2$

$h = v_it - \frac{1}{2}(9.81)t^2$

$h = v_it - 4.905t^2$

For the first stone:

$h_1 = 14.72t - 4.905t^2$

For the second stone

$h_2 = 29.44(t - 1) - 4.905(t - 1)^2$

$h_2 = 29.44(t - 1) - 4.905(t^2 - 2t + 1)$

$h_2 = 29.44t - 29.44 - 4.905t^2 + 9.81t - 4.905$

$h_2 = -4.905t^2 + 39.25t - 34.345$

$h_1 = h_2$

$14.72t - 4.905t^2 = -4.905t^2 + 39.25t - 34.345$

$24.53t = 34.345$

$t = 1.4 \, \text{ s}$

$h_1 = 14.72(1.4) - 4.905(1.4^2)$

$h = 10.994 \, \text{ m}$ *answer*